Peningkatan Kemampuan Menulis Narasi Dengan Menggunakan Media Gambar Berseri - Edy Sucanto (Education Research Center, 2025)
This study investigates the effectiveness of using series picture media to improve narrative writing skills among fourth-grade students at SDN Domas 1 Gresik. Traditionally, writing instruction in the classroom has been predominantly focused on theoretical aspects, where students are often asked to write based solely on their imaginations. Interviews with teachers revealed several challenges faced by students: a lack of interest in writing, difficulty organizing sentences, and an over-reliance on lecture-based teaching without engaging media, leading to disinterest and limited creativity. To address these issues, a classroom action research study was conducted over two cycles, incorporating series picture media into the writing lessons. The results indicate a significant enhancement in students' narrative writing abilities. The average narrative writing score increased from 60 in the pre-cycle stage to 62.58 after the first cycle and further to 67.52 after the second cycle. Additionally, the proportion of students meeting the minimum competency standard rose from 38.23% in the pre-cycle to 64.70% in the first cycle, and 85.29% in the second cycle, demonstrating a marked improvement of 47.06% overall. These findings highlight the effectiveness of using engaging and varied media, such as series pictures, in fostering student interest and improving their narrative writing skills. This approach not only enhances students’ creativity and engagement but also proves to be a valuable strategy in teaching narrative writing for elementary students. The study suggests that the integration of series picture media can be widely adopted to improve writing competencies in other educational settings